Characteristics of Electromagnetic Pulse Coupling into Annular Apertures - Yan-Peng Sun; Shi Zhang; Xiao-He An; Hong-Peng Sun (Institute of Advanced Engineering and Science, 2013)
Electromagnetic pulse (EMP) coupling into the annular apertures can disturb or damage much electronic equipment. To enhance electronic system’s capability of anti-electromagnetic interference, the finite difference time domain method (FDTD) was employed to study the characteristics of electromagnetic pulse coupling into the cavity enclosures with annular apertures. The coupling characteristics of annular apertures with different shapes (rectangle, square and circle) were discussed. It shows that, in the case of the same aperture area, the coupling energy of electromagnetic pulse into the circular annular aperture is smaller than that into the rectangular and the square ones. To the rectangular annular aperture, while the polarization direction of the incident electromagnetic pulse is perpendicular to the long side of the rectangular annular aperture, the coupling energy is larger when the aspect ratio of the rectangular annular aperture is larger. The coupling effect of incident pulse with short pulse width is obviously better than the one with longer pulse width. The resonance phenomenon of the coupled waveform occurs in the cavity. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3544